Future and emerging trends in language technology : machine learning and big data : second International Workshop, FETLT 2016, Seville, Spain, November 30-December 2, 2016, Revised selected papers /: machine learning and big data : second International Workshop, FETLT 2016, Seville, Spain, November 30-December 2, 2016, Revised selected papers. (2017) - Unknown
No abstract available